METHODS OF FORMING STUDENTS’ ECONOMIC THINKING IN TEACHING THE TAXATION COURSE (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article analyzes the theoretical foundations and practical methods of developing students’ economic thinking in the process of teaching the taxation course. Based on the content and objectives of the discipline, the study highlights effective ways to foster economic thinking through interactive teaching methods, problem-based learning, project-based instruction, digital technologies, and practical examples. Furthermore, the article examines advanced pedagogical practices implemented in Uzbekistan’s higher education system aimed at cultivating students’ economic thinking.